Site suitability analysis for locating a new mosque in district of Kulim, Kedah / Nur Awatif Othman and Nur Khairunnisa Sarah Anuar - Othman, Nur Awatif; Anuar, Nur Khairunnisa Sarah (Universiti Teknologi MARA (UiTM), 2024)
The study of the Site suitability analysis for locating a new mosque in the district of Kulim, Kedah by using ArcGIS Pro. The study will examine various factors that influence the suitability of a site for a mosque, including accessibility, proximity to residential areas, availability of land, and environmental considerations. For the objective, the aim is to identify the standard criteria for locating the optimal sites for mosque establishment, and to determine the most suitable locations for the establishment of a new mosque within the district Kulim, Kedah. The study will examine various factors that influence the suitability of a site for a mosque, including accessibility, proximity to residential areas, availability of land, environmental considerations, and compliance with local planning regulations.